Biosynthetic and catabolic pathways control amino acid δ2H values in aerobic heterotrophs - Silverman, Shaelyn N.; Wijker, Reto S.; Sessions, Alex L. (Frontiers in Microbiology, 2024)
The hydrogen isotope ratios (δ2HAA values) of amino acids in all organisms are substantially fractionated relative to growth water. In addition, they exhibit large variations within microbial biomass, animals, and human tissues, hinting at rich biochemical information encoded in such signals. In lipids, such δ2H variations are thought to primarily reflect NADPH metabolism. Analogous biochemical controls for amino acids remain largely unknown, but must be elucidated to inform the interpretation of these measurements. Here, we measured the δ2H values of amino acids from five aerobic, heterotrophic microbes grown on different carbon substrates, as well as five Escherichia coli mutant organisms with perturbed NADPH metabolisms. We observed similar δ2HAA patterns across all organisms and growth conditions, which-consistent with previous hypotheses-suggests a first-order control by biosynthetic pathways. Moreover, δ2HAA values varied systematically with the catabolic pathways activated for substrate degradation, with variations explainable by the isotopic compositions of important cellular metabolites, including pyruvate and NADPH, during growth on each substrate. As such, amino acid δ2H values may be useful for interrogating organismal physiology and metabolism in the environment, provided we can further elucidate the mechanisms underpinning these signals.